HAAR-WAVELET METHOD FOR DAMAGE DETECTION IN COMPOSITE STRUCTURES - Pysarenko, Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2025)
In recent years, wavelet analysis has emerged as a powerful mathematical tool for analyzing non-stationary signals, offering superior time-frequency localization compared to traditional Fourier analysis. This characteristic makes wavelet transforms particularly well-suited for processing signals obtained from structural health monitoring (SHM) systems, where damage often manifests as localized changes in the dynamic response of a structure. Among the various wavelet families, Haar-wavelets stand out due to their simplicity, computational efficiency, and ability to detect abrupt changes or discontinuities in signals. Their orthogonal and compact support properties make them an attractive choice for identifying localized damage events.